Processing of bulk nanolamellar tantalum and justification of strengthening by grain boundary pre-stressed model. (March 2021) - Goel, Sunkulp; Wang, Y.; Zhu, Y.M.; Liu, Y.; Wang, J.T.
Abstract: In the present work, bulk nano lamellar (NL) structured tantalum is fabricated via a two-step process, through primary grain refinement using equal channel angular pressing (ECAP) followed by a secondary geometrical refinement via rolling at different temperatures. Lamella boundary spacings with ~43 nm and ~62.9 nm after liquid nitrogen rolling (LNR) and room temperature rolling (CR), respectively, are produced exhibiting ~1.2 GPa tensile strength. A grain boundary pre-stress (GBp) model is formulated to explain the deviation of yield strength from the Hall-Petch relationship upon reaching the nanoscale. The GBp model explains the contribution to the rise in interface stress due to pre-existing dislocations at non-equilibrium grain boundaries, assisting the interfacial region to yield at lower stress value than the stress predicted by the confined layer slip (CLS) model. As the lamella thickness decreases with simultaneous increase in dislocation density, a critical value is reached where the interface stress will dominate the CLS stress leading to a fall of yield strength for the NL tantalum. The processing route A (strain path), small strain applied during each rolling pass and the suppression of a restoration mechanism at liquid nitrogen temperature are responsible for the near geometric refinement with a uniformity in the lamella structure. The limited tensile ductility of 90% rolled NL tantalum is associated with the formation of a large dislocation density, a smaller lamella spacing, and evolution of a strong (111)<110> fibre texture due to the body-centered cubic (BCC) crystal structure responsible for the formation of stiffened Σ3 grain boundaries. Highlights: Processing of Nano-lamellar (NL) tantalum exhibiting ~1.2 GPa tensile strength. Grain boundary pre-stress (GBp) model explaining deviation from Hall-Petch relationship. GBp model showing Inverse Hall-Petch behavior with smaller lamella thickness. Strong (111)<110> fibre texture responsible for increasing fraction of Σ3 grain boundary. Sudden fall of ductility due to formation of Σ3 grain boundaries.